Enantiopure planar chiral [2.2]paracyclophanes: Synthesis and applications in asymmetric organocatalysis. Issue 9 (24th July 2021) - Felder, Simon; Wu, Shiqi; Brom, Jules; Micouin, Laurent; Benedetti, Erica
Abstract: This short review focuses on enantiopure planar chiral [2.2]paracyclophanes (pCps), a fascinating class of molecules that possess an unusual three‐dimensional core and intriguing physicochemical properties. In the first part of the review, different synthetic strategies for preparing optically active pCps are described. Although classical resolution methods based on the synthesis and separation of diastereoisomeric products still dominate the field, recent advances involving the kinetic resolution of racemic compounds and the desymmetrization of meso derivatives open up new possibilities to access enantiopure key intermediates on synthetically useful scales. Due to their advantageous properties including high configurational and chemical stability, [2.2]paracyclophanes are increasingly employed in various research fields, ranging from stereoselective synthesis to material sciences. The applications of [2.2]paracyclophanes in asymmetric organocatalysis are described in the second part of the review. While historically enantiopure pCps have been mainly employed by organic chemists as chiral ligands in transition‐metal catalysis, these compounds can also be used as efficient catalysts in metal‐free reactions and may inspire the development of new transformations in the near future. Abstract : Planar chiral [2.2]paracyclophanes (pCps) constitute a fascinating class of molecules which possesses an unusual three‐dimensional core and intriguing physicochemical properties. This short review focuses on the synthesis of enantiopure pCps and their application in asymmetric organocatalysis.